Skip to content

Commit

Permalink
Make terms clearer using boolean expressions
Browse files Browse the repository at this point in the history
I tried to make it clear that a CDNL terms is a conjunction of negations of conjunctions by desugaring them into boolean expressions.

I'm having trouble making what's going on sufficiently clear since we need to write the negations out to apply transformation rules to them, but then they are not incompatibilities anymore but constraints that must be satisfied.
  • Loading branch information
konstin committed Apr 9, 2024
1 parent bc0e91e commit 48bda98
Showing 1 changed file with 16 additions and 12 deletions.
28 changes: 16 additions & 12 deletions src/internals/incompatibilities.md
Original file line number Diff line number Diff line change
Expand Up @@ -89,28 +89,32 @@ With incompatibilities, we would note
\Rightarrow \quad \\{ a: T_a, c: \overline{T_c} \\}. \\]

This is the simplified version of the rule of resolution.
For the generalization, let's reuse the "more mathematical" notation of conjunctions
for incompatibilities \\( T_a \land T_b \\) and the above rule would be
For the generalization, let's write them as [boolean expressions][boolean_expression].

\\[ T_a \land \overline{T_b}, \quad
T_b \land \overline{T_c} \quad
\Rightarrow \quad T_a \land \overline{T_c}. \\]
\\[ \neg (T_a \land \overline{T_b}) \quad \land \quad
\neg (T_b \land \overline{T_c}) \quad
\Rightarrow \quad \neg (T_a \land \overline{T_c}). \\]

In fact, the above rule can also be expressed as follows

\\[ T_a \land \overline{T_b}, \quad
T_b \land \overline{T_c} \quad
\Rightarrow \quad T_a \land (\overline{T_b} \lor T_b) \land \overline{T_c} \\]
\\[ \neg (T_a \land \overline{T_b}) \quad \land \quad
\neg (T_b \land \overline{T_c}) \quad
\Rightarrow \quad \neg (T_a \land (\overline{T_b} \lor T_b) \land \overline{T_c}) \\]

since for any term \\( T \\), the disjunction \\( T \lor \overline{T} \\) is always true.
In general, for any two incompatibilities \\( T_a^1 \land T_b^1 \land \cdots \land T_z^1 \\)
and \\( T_a^2 \land T_b^2 \land \cdots \land T_z^2 \\) we can deduce a third,
called the resolvent whose expression is
In general, for any two incompatibilities \\( \\{ a: T_a^1, \cdots, z: T_z^1 \\} \\) and
\\( \\{ a: T_a^2, \cdots, z: T_z^2 \\}, \\)
or

\\[ (T_a^1 \lor T_a^2) \land (T_b^1 \land T_b^2) \land \cdots \land (T_z^1 \land T_z^2). \\]
\\[ \neg (T_a^1 \land T_b^1 \land \cdots \land T_z^1) \land \neg (T_a^2 \land T_b^2 \land \cdots \land T_z^2), \\]
we can deduce a third, called the resolvent whose expression is

\\[ \neg ((T_a^1 \lor T_a^2) \land (T_b^1 \land T_b^2) \land \cdots \land (T_z^1 \land T_z^2)). \\]

In that expression, only one pair of package terms is regrouped as a union (a disjunction),
the others are all intersected (conjunction).
If a term for a package does not exist in one incompatibility,
it can safely be replaced by the term \\( \neg [\varnothing] \\) in the expression above
as we have already explained before.

[boolean_expression]: https://en.wikipedia.org/wiki/Boolean_expression#Boolean_operators

0 comments on commit 48bda98

Please sign in to comment.